Expand (7+m)³ pls fast
Answers
Answered by
2
Answer:
(7 + m)3 =(7)3 + [ 3 ×(7)2 ×(m)] + [ 3 ×(7)×(m)2] +(m)3
{ ∵(a + b)3 = a3 + 3a2b + 3ab2 + b3 }
= 343 +(3 × 49)m +(3 × 7)m2 + m3
= 343 + 147m + 21m2 + m3
Step-by-step explanation:
Have a great time buddy
Answered by
2
Refer to the attachment.. hope it helps
Please mark me as a brainliest ❤️❤️
Bye ☺️
Please mark me as a brainliest ❤️❤️
Bye ☺️
Attachments:
![](https://hi-static.z-dn.net/files/dcf/c92c11d17ae7ef41c7f8afc5d9a49720.png)
Similar questions